Study of Infectious Diseases Among Children of Kindergarten Age - Umurzakova Muattar Rustamovna (Zien Journals, 2023)
The review is devoted to the analysis of the incidence of whooping cough in children in the age group of 5–7 years, as well as immunization strategies with DTP drugs in foreign countries. Mass vaccination against whooping cough began in the middle of the 20th century, which contributed to a decrease in morbidity and mortality from this infection, but in the last decade there has been an opposite trend, consisting in an increase in the proportion of patients among preschool, school-age children and adults
Keywords: acellular whooping cough vaccine; immunity to whooping cough; vaccine